The impact of project-based learning on university physics education: enhancing cognitive skills and core competencies - Wang, Chenglong; Song, Lirong; Jiang, Jun (Frontiers in Psychology, 2025)
BackgroundProject-Based Learning (PBL) has been proposed as an alternative to traditional lecture-based instruction in university physics courses. This study examines the effects of PBL on undergraduates' conceptual understanding, problem-solving skills, practical competencies, engagement, and motivation.MethodsA mixed-methods quasi-experimental design was employed with 150 physics majors from three universities in Harbin, China. Participants were stratified by key demographics and baseline physics knowledge, then randomly assigned to a PBL group (n = 75) or a lecture-based control group (n = 75). Quantitative data were gathered via standardized pre- and post-tests; effect sizes were calculated (Cohen's d). Qualitative data were obtained through structured classroom observations and semi-structured interviews. Multiple regression analyses—controlling for baseline knowledge—evaluated predictors of post-test performance (R2, significance tests), with diagnostic checks for normality and multicollinearity (VIF).ResultsThe PBL group demonstrated significantly greater gains in conceptual understanding (Cohen's d = 1.85) and problem-solving ability than the control group (Cohen's d = 0.72). Observational and interview data revealed increased student engagement, collaboration, and real?world application of physics principles. Regression analysis indicated that initial academic performance and in-class engagement were significant predictors of post-test success (R2 = 0.65, p < 0.001), with VIF values below 2 confirming minimal multicollinearity.ConclusionsFindings suggest that PBL substantially enhances both cognitive and practical skills, fostering critical thinking and teamwork in university physics education. Practical implementation challenges—such as increased preparation time and the need for specialized facilitation—remain. Future research should explore the long-term impact of PBL in varied educational settings and its adaptability across disciplines.